An Overview of Corporate Social Responsibility in the Hospitality and Tourism Sector of Pakistan - Barza Iftikhar Mir (UW Journal of Management Sciences, 2022)
Purpose: The purpose of the paper is to deal with Corporate Social Responsibility with reference to the hospitality and tourism sector of Pakistan. Due to the excessive involvement of the corporate social responsibility in each business, there is a need to identify the Corporate social responsibility in the tourism sector from a business point of view. Design/Methodology: The study is based on the qualitative design in which the critical review of the literature methodology is being used. Findings: The study explored the key areas of Corporate Social Responsibility in the tourism sector of Pakistan. Key findings suggest that the factors that contribute more in the tourism are the rich culture of Pakistan, art and film industries, and extensive landscape of Pakistan. Further factors are needed to be explored because this area is vast and required more research. Moreover, China-Pak Economic Corridor (CPEC) is a great step that can improve the tourism culture in Pakistan by making linkages with the neighboring countries. Implications: The gaps identified in the study suggest that the security system as well as the law and order situation and policy implication for the international tourist in Pakistan needs to be improved. Moreover, there is also a need to improve the tourist resorts and residence to provide them an attractive environment. It is also suggested to conduct international festivals in the country that may promote tourism and hospitality. Further, there is a need to explore the interest of the tourist and to build close linkages with the rest of countries around the world.